Escalas against three kinds of walls - González Vigil, Ricardo (2023)
In this article we propose that Escalas (1923), by César Vallejo, attacks three kinds of walls, that is to say, it seeks to free itself from them. These are the walls of action, thought and literary creation. This can be identified in the different stories that compose the book, in which we can see Vallejo’s impetus to free himself from conventional aspects and reasoning which, on the one hand, determine justice and truth and, on the other, exclude sensibility, intuition and the cognitive attempt, which is incomplete and perfectible. In this way, the epigraph of Escalas, authored by Antenor Orrego, is in line with Vallejo’s proposal: «First thought, then reason».